PARAOKSONAZ - BALCI EKMEKÇİ, Özlem and DONMA, Orkide and EKMEKÇİ, Hakan (Cerrahpaşa Medical Journal, 2014)
Background.- Paraoxonase (PON1) is a calcium-dependent esterase that is a component of plasma high density lipoprotein (HDL), and hydrolazes organophosphates (e.g. paraoxon, diazooxon), aromatic carboxylicacid esters and nerve gases. Paraoxonase protects low density lipprotein (LDL) and HDL from oxidation induced by either copper (Cu) ion, or free radicals. This protection is probably related to PON's ability to hydrolyze some oxidized phospholipids and/or cholestryl linoleate hydoperoxidases which are present in Ox-LDL. PON1's free sulpfhydryl group of cystein-284 is required for PON1's ability to protect LDL against oxidation.